Effects of pressure-controlled ventilation-volume guaranteed on children undergoing thoracic surgery: a prospective, randomized controlled trial - Wang, Lei; Zhu, Yi; Zhu, Shili; Yan, Lulu; Du, Zhen; Xiao, Ting; Qu, Shuangquan (Frontiers in Medicine, 2025)
BackgroundChildren have higher morbidity and mortality than adults during thoracic surgery with one-lung ventilation (OLV), reducing the incidence may in part be achieved by the use of appropriate mechanical ventilation mode. This study evaluated whether pressure-controlled ventilation-volume guaranteed (PCV-VG) reduces intrapulmonary shunt (Qs/Qt) and ventilator-induced lung injury (VILI) in pediatric patients.MethodsEighty children underwent thoracic surgery requiring OLV were randomly divided into PCV-VG group and volume-controlled ventilation (VCV) group. The PCV-VG group utilized the PCV-VG during surgery, whereas the other group employed the VCV. The parameter settings during two-lung and OLV were consistent between the groups. The primary outcome comprised the Qs/Qt fraction. The secondary outcomes encompassed respiratory parameters, blood gas analysis results, the occurrence of postoperative pulmonary complications (PPCs), and more.ResultsFollowing PCV-VG implementation, the median Qs/Qt during OLV exhibited a significant improvement (18.2 to 12.7 at T2, 11.4 to 9.1 at T3, p < 0.0001). Additionally, compared with VCV, PCV-VG improved oxygenation during OLV (higher PaO2, PaO2/FiO2, and other oxygenation indices), reduced airway pressure during OLV (25cmH2O to 20cmH2O at T2, p < 0.0001), and lowered the incidence of PPCs [38.5 to 7.3%, adjusted odds ratio (OR) 0.13, 95% confidence interval (CI): 0.03–0.50, p = 0.001], shortened the duration of postoperative mechanical ventilation [120 min to 110 min, difference (95% CI), 20 (0 to 40), p = 0.036].ConclusionImplementation of PCV-VG for children undergoing thoracic surgery demonstrated significant benefits. It can improve Qs/Qt, increase oxygenation, reduce airway pressure, and alleviate VILI during OLV.Clinical trial registrationClinicaltrials.gov, identifier ChiCTR2200065237.